Assessment of prostate imaging reporting and data system version 2.1 false-positive category 4 and 5 lesions in clinically significant prostate cancer - Wang, Xiangyu; Liu, Weizong; Lei, Yi; Wu, Guangyao; Lin, Fan (Abdominal imaging, 2021)
Purpose To determine the incidence and false-positive rates of clinically significant prostate cancer (CSPC) in prostate imaging reporting and data system (PI-RADS) category 4 and 5 lesions using PI-RADS v2.1. Methods One hundred and eighty-two lesions in 169 subjects with a PI-RADS score of 4 or 5 were included in our study. Lesions with clinically insignificant prostate cancer (CIPC) or benign pathologic findings were reviewed and categorized by a radiologist. The initial comparison of demographic and clinical data was performed by t -test and χ 2 test, and then the logistic regression model was used to determine factors associated with CIPC or benign pathological findings. Results Of the 182 PI-RADS category 4 and 5 lesions, 84.6% (154/182) were prostate cancer (PCa), 73.1% (133/182) were CSPC, and 26.9% (49/182) were CIPC or benign pathologic findings. The false-positive cases included 44.9% (22/49) with inflammation, 42.9% (21/49) with CIPC, 8.2% (4/49) with BPH nodules and 4.1% (2/49) with normal anatomy cases. In multivariate analysis, factors associated with CIPC or benign features included those in both the peripheral zone (PZ) and central gland (CG) (odds ratio [OR] 0.062; p = 0.003) and a low prostate-specific antigen density (PSAD) (OR 0.34; p = 0.012). Conclusion The integration of clinical information (PSAD and lesion location) into mpMRI to identify lesions helps with obtaining a clinically significant diagnosis and decision-making.